2015
DOI: 10.1016/j.str.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Surface Density-Induced Pleating of a Lipid Monolayer Drives Nascent High-Density Lipoprotein Assembly

Abstract: Summary Biogenesis of high density lipoproteins (HDL) is coupled to the transmembrane protein, ATP-binding cassette transporter A1 (ABCA1), which transports phospholipid (PL) from the inner to the outer membrane monolayer. Using a combination of computational and experimental approaches, we show that increased outer lipid monolayer surface density driven by excess PL or by membrane insertion of amphipathic helices, results in pleating of the outer monolayer to form membrane-attached discoidal bilayers. Apolipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…Indeed, additives like isopropanol can induce a lipid-boundlike structure to otherwise lipid-free apoA-I (42). Crystal packing and other factors could also be responsible (43).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, additives like isopropanol can induce a lipid-boundlike structure to otherwise lipid-free apoA-I (42). Crystal packing and other factors could also be responsible (43).…”
Section: Discussionmentioning
confidence: 99%
“…Direct interaction between apoA-I and ABCA1 has been shown (30)(31)(32). It has also been reported that ABCA1 at the PM produces membrane deformation sites where apoA-I interacts and solubilizes lipids present in these domains to generate nascent HDL ( 33,34 ). These results lead one to speculate that the lipid compositions of nascent HDL may refl ect those of a membrane domain where nascent HDL is assembled.…”
Section: Cell Fractionationmentioning
confidence: 91%
“…The unique structural properties of lanosterol may thus allow it to be more mobile at the PM for ABCA1-dependent release. It was shown that ABCA1 creates a specifi c lipid-packing deformation site at the PM, and apoA-I recognizes and solubilizes such membrane domains to generate HDL ( 33,34 ). HDL particles generated by ABCA1 are cholesterol-rich and have similar lipid composition to lipid rafts ( 53 ), suggesting that the ABCA1/ apoA-I system generates HDL at a membrane domain containing signifi cant amounts of cholesterol.…”
Section: Abca1 Is Present In the Cholesterol-rich Membrane Domainmentioning
confidence: 99%
“…Most of the apoA-I binds with high affinity to lipid sites in the PM created by the PL translocase activity of the transporter. These lipid domains in the PM to which apoA-I binds protrude into the extracellular space (105)(106)(107) and are thought to be the sites of HDL particle assembly. It has been suggested that apoA-I must interact with ABCA1 before it can interact with PL in the PM (108).…”
Section: Abca1-mediated Pl-apoa-i Interactionmentioning
confidence: 99%